2022
DOI: 10.1029/2021gb007057
|View full text |Cite
|
Sign up to set email alerts
|

Latitude, Elevation, and Mean Annual Temperature Predict Peat Organic Matter Chemistry at a Global Scale

Abstract: Peatlands contain a significant fraction of global soil carbon, but how these reservoirs will respond to the changing climate is still relatively unknown. A global picture of the variations in peat organic matter chemistry will aid our ability to gauge peatland soil response to climate. The goal of this research is to test the hypotheses that (a) peat carbohydrate content, an indicator of soil organic matter reactivity, will increase with latitude and decrease with mean annual temperatures, (b) while peat arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 85 publications
2
9
0
Order By: Relevance
“…Previous studies have shown that Sphagnum -derived peat that is more typical in acidic northern peatlands has a lower C:OM ratio than peat derived primarily from herbaceous vegetation and woody plants [ 20 , 39 ]. Indeed, Verbeke [ 33 ] used FTIR to show that concentrations of carbohydrates decreased relative to aromatics in samples taken from the same sites as those used in our study. This would result in a loss of organic O and C and a relative increase in C-C bonding resulting in more C relative to OM in deeper peat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Sphagnum -derived peat that is more typical in acidic northern peatlands has a lower C:OM ratio than peat derived primarily from herbaceous vegetation and woody plants [ 20 , 39 ]. Indeed, Verbeke [ 33 ] used FTIR to show that concentrations of carbohydrates decreased relative to aromatics in samples taken from the same sites as those used in our study. This would result in a loss of organic O and C and a relative increase in C-C bonding resulting in more C relative to OM in deeper peat.…”
Section: Discussionmentioning
confidence: 99%
“…We quantified global variation in peatland C and N concentrations and organic matter content in 1226 individual peat samples at different depths, from 436 cores, collected across 24 countries and six continents ( Fig 1 ). The samples are part of a larger project characterizing the geochemistry and microbial communities in global peatlands ([ 33 ], Global Peatland Microbiome Project). An important aim of the overall project was to generate a common data set across peatlands that was robust enough to allow global-scale comparisons but was also flexible enough to be useful for local-scale research projects at each site.…”
Section: Methodsmentioning
confidence: 99%
“…Lower water tables consistently increase ecosystem respiration (ER) in the short term, but whether these increases are compensated for by primary production depends on plant community changes (Bubier et al, 2003; Chimner et al, 2017; Juszczak et al, 2012; Laiho, 2006; Riutta et al, 2007; Zhong et al, 2020). Hypoxic conditions below the water table depress peatland decomposition rates, indicating that persistent labile organic material in peatland C sinks may be readily decomposed when not waterlogged (Laiho, 2006), especially in colder northern sites (Verbeke et al, 2022). Hydrology influences redox conditions, gas diffusion, and nutrient availability (Holden, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic conditions below the water table depress peatland decomposition rates, indicating that persistent labile organic material in peatland C sinks may be readily decomposed when not waterlogged (Laiho, 2006), especially in colder northern sites (Verbeke et al, 2022). Hydrology influences redox conditions, gas diffusion, and nutrient availability (Holden, 2005).…”
mentioning
confidence: 99%
“…This indicates that hemicellulose content and composition play an essential role in the stability of surface peat. Increased temperatures and latitudinal gradients were found to influence the carbohydrate content of peat, indicating that differences in specific carbohydrate linkages are important for peat stability. Moreover, it was found that CO 2 releases were twice as high in surface peat (2.5–5 cm) than in older peat (10–12.5 cm) .…”
Section: Discussionmentioning
confidence: 99%